Exploring Digital Storytelling as a Pedagogical Tool for Emergent Literacy Skills - Gupta, Noyonika; Sharma, Arushi (JOURNAL OF INDIAN EDUCATION, 2023)
The present study investigates the effectiveness of a multi-modal intervention utilising digital storytelling and art to enhance emergent literacy skills, particularly Oral Vocabulary and Comprehension, and promotes parental engagement in the learning process among children aged 3–6 years. Positive changes were noted, attributing success to music in stories, word frequency, familiar contexts, reinforcing concepts through art, child-centric approach, and active adult-child engagement. Despite limitations in sample size and tools, the research remains relevant in the context of existing literature emphasising on the critical age of 3–6 years for developing emergent literacy skills due to advancements in cognitive representational ability and symbolic thinking during this phase. Moreover, the intervention’s potential benefits are particularly significant for children from lower socioeconomic backgrounds, where exposure to literacy-related materials and environments might be limited. The study’s implications extend far, showcasing the potential of digital storytelling and art-based pedagogies in building emergent literacy skills during the pre-primary stage.